Creating Scripts for Crisis Communication: COVID-19 and Beyond. (January 2021) - St.Amant, Kirk
Individuals act on information that connects to their daily lives. In emergencies like the COVID-19 pandemic, these connections are central to maintaining individual health and community safety. Making such connections requires an understanding of audience perceptions; the better technical communicators address these perceptions, the more successful their materials can be. This article presents a cognitive framework, based on script theory, to help identify and address such factors in the COVID-19 crisis and in future public health challenges.